Validitas Isi dan Reliabilitas Instrumen Penilaian Harian Mata Pelajaran Bahasa Arab MI Manarul Islam Malang - Maghfirotunnisa, Alfi; Nur Qomari,; Asbarin, (Shaut al Arabiyyah, 2023)
The aims of this research are: 1) to find out the content validity of the Arabic subject in the Daily Assessment (PH) at MI Manarul Islam Malang. 2) to determine the reliability of the Arabic language subject in the Daily Assessment (PH) in the form of multiple choice questions and entries at MI Manarul Islam Malang. This research is a type of quantitative research with data collection techniques through tests from a research sample of 36 students in grades 4A and 4B for the 2022/2023 academic year as well as analysis of testing the test instrument items consisting of validity tests and reliability tests evaluated using SPSS version 22 In the daily assessment of a foreign language subject, namely Arabic, student answer sheets are used to assess the validity of the items and the reliability of the test instrument test (Arabic). The results of this study are where the items in the daily assessment of the MI Manarul Islam Malang Arabic subject in the multiple choice question validity test consist of 20 questions, 12 of which are classified as valid while the other 8 items are classified as invalid. While the questions in the form of fields consisting of 10 questions are classified as valid as a whole. In the reliability test, the multiple choice questions were declared to have high reliability. While the results of the reliability test in the form of filled in items were stated to have very high reliability.